SEEDING SUSTAINABILITY IN THE WEST (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The purpose of this Essay is to examine the meaning of sustainability in the context of the West, a task I took on, with some trepidation, for the 15th Annual Wallace Stegner Symposium at the University of Utah's S.J. Quinney College of Law. Addressing the question of sustainability is daunting because it is an all-encompassing topic, and because the West-both its people and its landscapes-is so diverse, and its environment so variable. The task is also daunting because an unvarnished assessment of the current situation in the West leaves one with no alternative but to conclude that our region is far removed from any workable definition of sustainability. On the other hand, it is a region that is still full of possibility, an expansive area, still sparsely settled, where many small but important efforts are moving toward sustainability in small steps, while clarifying the objective and demonstrating the path forward.